INNOVATIVE TEACHING METHODS: A BLEND OF THEORY AND PRACTICE IN TRAINING FUTURE MEDICAL PROFESSIONALS - Трубенко, Олександр; Федосєєва, Ольга; Скалько, Ігор (SWorldJournal, 2025)
The article focuses on innovative teaching methods. It should be noted that teaching practices update in medical education is a necessary step to ensure high-quality training for future medical professionals. It is characterized by a blend of theory and p